1998
DOI: 10.1038/bjc.1998.365
|View full text |Cite
|
Sign up to set email alerts
|

Is chromosome 9 loss a marker of disease recurrence in transitional cell carcinoma of the urinary bladder?

Abstract: Summary Investigation of transitional cell carcinoma of the urinary bladder (TCC) patients classified by recurrence and/or progression has demonstrated that loss of chromosome 9, as detected by FISH analysis of the pericentromeric classical satellite marker at 9q12, occurs early. A total of 105 TCCs from 53 patients were analysed in situ by two independent observers for loss of chromosome 9 using quantitative fluorescence in situ hybridization (FISH). All 53 primary tumours were evaluated for chromosomes 9, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 7 publications
2
30
1
Order By: Relevance
“…Jung et al 60 reported a similar association with recurrence but others have not 61 and some studies suggest that LOH on 9q rather than 9p21 is associated with tumor recurrence. 62,63 In the present study we found no association with tumor grade or stage. In light of the finding that large tumor size is associated with 9p21 alterations, 50 it is worth noting that the 53 tumors from our previous series that were re-assessed here are those for which we still had DNA remaining and therefore represented larger tissue samples.…”
Section: Rtq-pcr (contrasting
confidence: 78%
“…Jung et al 60 reported a similar association with recurrence but others have not 61 and some studies suggest that LOH on 9q rather than 9p21 is associated with tumor recurrence. 62,63 In the present study we found no association with tumor grade or stage. In light of the finding that large tumor size is associated with 9p21 alterations, 50 it is worth noting that the 53 tumors from our previous series that were re-assessed here are those for which we still had DNA remaining and therefore represented larger tissue samples.…”
Section: Rtq-pcr (contrasting
confidence: 78%
“…FISH was performed as previously described [27,28]; brie¯y, slides were pretreated with 0.2 mol/L HCl, 8% sodium thiosulphate at 80uC and 0.5% pepsin at 37uC. Sections were post-®xed in 10% neutral buffered formalin.…”
Section: Methodsmentioning
confidence: 99%
“…Control sections from normal bladder tissue obtained from post mortem normal bladder were included in the analysis. Values for disomy were derived from the analysis of these tissue sections as previously reported (Bartlett et al, 1998;Watters et al, 2000).…”
Section: Scoring Criteriamentioning
confidence: 99%
“…Previous research within this laboratory demonstrated that polysomy of chromosomes 9, 7 and 17 are associated with recurrence (Bartlett et al, 1998, Watters et al, 2000, but that these genetic events are not linked with polyploidy (Bartlett et al, 1999). A small study within this laboratory investigating the drug metabolising enzyme NAT2 (the gene is located at chromosome 8p22) in TCC recurrence or progression suggested that polysomy 8 was associated with disease progression .…”
mentioning
confidence: 96%
See 1 more Smart Citation